Effect of Pectin on the processing and preservation of Strawberry (Fragaria ananassa) jam and jelly (International Journal of Natural Sciences, 2012)
This study was conducted to investigate the interaction of different concentration of pectin and its dissipation from processing to storage of strawberry (Fragaria ananassa) jam and jelly. The fruits were collected from local market of Sylhet, Bangladesh. The analysis showed juice contains acidity 1.14±0.01 %, total sugar 0.61±0.06 %, TSS 8.98±0.03 % and pulp restrain acidity 01.02±0.01 %, total sugar 5.04±0.06 %, and TSS 8.57±1.36 %. Jam and jelly were prepared with 0.5%, 1% and 1.5% pectin. Potassium metabisulphate (KMS) was added as preservative in a required quantity. Study showed pectin do not significantly interact with quality attributes of processed product. During six month of storage at ambient temperature (27°C to 34°C) no mentionable changes were found. But PH of the products (jam and jelly) was slightly increased. At six month red color of 0.5 % pectin containing jam slightly faded and cohesiveness of 1% and 0.5 % pectin containing jelly considerably changed. A taste panel consisting 10 panelists adjudged the acceptability of the samples. The consumers preferences were measured by statistical analysis. Among the samples, both jam and jelly made with 1.5% pectin was commended as best product by the panelists at p